Analisis Problem Tree Pada Kebijakan Pembayaran Parkir Elektronik di Kota Surabaya - Abdillah, Taqiyyudin; Muhammad Farrel Langit Arundaya; M. Noer Falaq Al Amin (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
Abstract. The Surabaya City Government recently implemented a new policy aimed at increasing the efficiency and transparency of parking fee collection. The new policy focuses on the use of electronic payment methods, especially QRIS, to reduce the possibility of leaks and increase parking attendants' income. By using QRIS, the government hopes to provide the public with a safe and convenient way to pay for parking, while ensuring that all parking charges are recorded accurately. To assess the effectiveness of this new policy, researchers will analyze the public's response to non-cash payments, such as QRIS, as well as the impact of this payment system on parking attendants' income. Researchers will use the Literature Review and Problem Tree Analysis method to conduct a comprehensive analysis of the benefits and potential challenges related to this new policy. Overall, the government hopes this new policy will not only improve the efficiency and transparency of parking fee collection but also increase the income of parking attendants and provide the public with a convenient and safe way to pay for parking.